Khse-muoy in the Kingdom of Cambodia - Tangted, Watchara; Chonpairot, Jarernchai; Pikulsri, Chalermsak (วารสารพิชญทรรศน์, 2018)
The Khse-muoy is a traditional Cambodian chordophone instrument played by strumming and is capable of producing harmonic notes. Khse-muoy is a primary instrument in traditional Cambodian ensembles and provides music and entertainment for Cambodian traditions, celebrations, ceremonies and rituals. This qualitative study aimed at : 1) to study about the teaching process of Khse-muoy in Cambodia and 2) to study about the role of Khse-muoy in Cambodian traditions. The field data were obtained through interviews and observations with the Key informants which consisted professional Khse-muoy musicians and teachers. Casual informants, in Cambodia October 2014 to September 2015. The results of the study showed that Teaching Khse-muoy in the Kingdom of Cambodia are consistent and follow oral tradition and can be classified into 4 aspects of 1) teachers characteristics, 2) teaching location, 3) content and 4) teaching mediums. The primary instructors of Khse-muoy are the professional Khse-muoy musicians themselves but can also include senior students which aid in the lessons and practices by providing students with a model to follow on. The location of the lessons and teachings is different according to each teacher and it is usually the Khse-muoy musicians themselves who will decide on the location of the lessons. The content of the lessons on Khse-muoy are compiled directly by the Khse-muoy teachers and usually encompasses music and songs that accompany tradition activities. The learning materials of Khse-muoy may differ from teacher to teacher but the essential medium is the Khse-muoy instrument itself and not all classes and lessons are performed by following music notes. The majority of lessons are usually oral lessons and demonstrations by the teacher and senior students. And current the role of khse-muoy in the Cambodian tradition in the three most popular traditions for Khse-muoy are phiti rieb-ka (wedding ceremony), phiti kat so (cork shaving ceremony) and phiti-ara (healing ritual).